Development and Evaluation of a Transition Model for Adolescents With Inflammatory Bowel Disease Moving From Pediatric to Adult Surgical Care: Report of a Quality Improvement Project in a Swedish Setting. Issue 1 (January 2022) - Bergström, Jenny; Dellenmark-Blom, Michaela; Gatzinsky, Vladimir; Abrahamsson, Kate; Bräutigam, Matilda; Gatzinsky, Cathrine
Abstract : Background: There is a need for a transition model for patients with inflammatory bowel disease (IBD) moving from pediatric to adult surgical care. Aim: The aim of this study was to report the development and evaluation of a transition model for adolescents with IBD from pediatric to adult surgical care in a Swedish setting. Methods: A multidisciplinary team conducted a literature search on the needs of patients with IBD moving from pediatric to adult surgical care. This was followed by a consensus discussion to aid the creation of a surgical transition model. Between 2018 and 2020, eight of 12 adolescents who had undergone IBD surgery and were transferred to adult care answered a 25-item questionnaire regarding their health and quality of care. Results: The main components of the surgical transition model are as follows: The adolescents are given more responsibility for their IBD management; they meet staff without parents; they are given information about the transfer at the age of 14 years; if willing, they undergo a rectoscopy without anesthesia; and they complete a transition checklist and have a first meeting with the pediatric and adult surgical staff. After transfer, respondents rated their health positively but described some everyday life limitations. They reported sufficient preparation before transfer, positive attitudes by healthcare professionals, and parental support. They felt they had been given enough information before the stoma surgery and were satisfied with availability of the nurse and the stoma location. Discussion: A surgical transition model from pediatric to adult care for patients with IBD is motivated from the adolescents' perspectives. More research is warranted.